Truncating the Drive of Yahoo-Yahoo in Nigeria: The Relevance of Surah At-Takhathur - Muhammad, Usman Jimoh; Sulaiman, Muhammad (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2024)
The paper looks at the increasing nature of cybercrime activities, particularly yahoo-yahoo in Nigeria. The paper adopted descriptive and evaluative methods of research to gather and analyze relevant data. The paper identifies some cases of this crime in society to validate its position. The findings show that the influence of peer groups, parental and societal support, unemployment, and many others account for the growing nature of crime in society. While the paper posits that the criminal gain from Yahoo activities is temporal, it draws attention to the concept of life after death and accountability as enumerated in Qur’an chapter 102 as a deterrence to the people’s inordinate quest for wealth at all costs. The paper recommends a more robust orientation of people by both religious leaders and appropriate government agencies on the need to have the human mind and no devilish nature. The government and the well-to-do people in society are also encouraged to join hands to address the problem of unemployment.